Study on Shear Characteristics of Interface between Frozen Soil and Pile during Thawing Process in Permafrost Area - Ying Zhao; Xuesong Mao; Qian Wu; Wanjun Huang; Yueyue Wang (Advances in Civil Engineering)
In permafrost areas, the degradation of permafrost greatly affects the stability of concrete pile composite foundations. Hence, direct shear tests were carried out to analyze the effect of the rising frozen temperature, moisture content, and normal stress on the mechanical properties of the frozen soil-pile interface during the thawing process of permafrost. A constitutive model was established to describe the shear stress-displacement variation law of interface, considering the hydrothermal coupling effect. The results show that the frozen strength of the interface was provided by the ice crystal structure formed at the interface, and its area increases with increasing water content. The whole shear process can be divided into three stages: the prepeak stage with growing shear stress, the postpeak stage with deep dropping shear stress, and the shear stress reconstruction stage. The peak frozen strength was positively correlated with water content and normal stress, however, it was negatively correlated with the rising frozen temperature. The residual frozen strength has a linear relationship with normal stress and water content, however, it shows different regularity with rising frozen temperature at different water content. Moreover, the Gompertz model prediction results are in good agreement with the experimental results. This model can describe well the stress-displacement variation law of interface with different rising frozen temperature and water content.